2007
DOI: 10.1007/s11214-007-9192-4
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Influence of the Active Young Sun on the Early Atmospheres of Earth, Venus, and Mars

Abstract: Because the solar radiation and particle environment plays a major role in all atmospheric processes such as ionization, dissociation, heating of the upper atmospheres, and thermal and non-thermal atmospheric loss processes, the long-time evolution of planetary atmospheres and their water inventories can only be understood within the context of the evolving Sun. We compare the effect of solar induced X-ray and EUV (XUV) heating on the upper atmospheres of Earth, Venus and Mars since the time when the Sun arriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
142
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(151 citation statements)
references
References 164 publications
(269 reference statements)
8
142
1
Order By: Relevance
“…It is therefore possible that these planets experience little water escape, as on Earth (Lammer et al 2003;Kulikov et al 2007;Selsis et al 2007). We note that an extreme case for water escape has been observed for a hot Neptune (Ehrenreich et al 2015).…”
Section: Circular Orbitsmentioning
confidence: 73%
“…It is therefore possible that these planets experience little water escape, as on Earth (Lammer et al 2003;Kulikov et al 2007;Selsis et al 2007). We note that an extreme case for water escape has been observed for a hot Neptune (Ehrenreich et al 2015).…”
Section: Circular Orbitsmentioning
confidence: 73%
“…In recent studies by Kulikov et al (2006Kulikov et al ( , 2007, Lammer et al (2006Lammer et al ( , 2008, Lundin et al (2007), Tian et al (2008a, b) and illustrated in Fig. 4 it was shown that enhanced solar EUV radiation and plasma (winds, CMEs) should result in permanent forcing of the upper planetary atmospheres, which can ionize, heat, expand, chemically modify, and erode it during the early phase of a planetary lifetime.…”
Section: Solar Activity Response Of Planetary Upper Atmospheresmentioning
confidence: 96%
“…When the temperature of the thermosphere is large, a significant fraction of the light constituents of the upper atmosphere attain velocities above the escape value, and the thermosphere may even become non-hydrostatic and start to expand accompanied by adiabatic cooling to several planetary radii (Chassefière, 1996;Tian et al, 2005Tian et al, , 2008aTian et al, , b, 2009Kulikov et al, 2007;Lammer et al, 2008).…”
Section: Solar Activity Response Of Planetary Upper Atmospheresmentioning
confidence: 99%
See 1 more Smart Citation
“…Pepin 1991), atmospheric loss because of escape to space (e.g. Kulikov et al 2007;Kulikov et al 2006) or incorporation into planetary surface material. But these processes are not known for the Gl 581 system.…”
Section: Model Input For Gl 581 and Performed Runsmentioning
confidence: 99%